A Study of the Morphological Variation in the Shape and Size of Sella Turcica in the Population of Benghazi - Mohammed, Fatimah Alhadi; Alzentani, Seraj; Ayad, Iman; Werfalli, Mahmoud Mohammed (Scientific Journal of University of Benghazi, 2021)
Sella Turcica is a saddle-shaped depression, located in the middle cranial fossa on the upper surface of the sphenoid bone. The morphology of Sella Turcica is significant for evaluating treatment outcomes and late developmental changes and especially in assessing the cranial morphology. This study aims to estimate the normal variation in the shape and measurement of Sella Turcica (length, depth, antero-posterior diameter) as well as the differences between genders and age groups. This research is a descriptive cross-sectional study and included adult patients (N=100) in Al-Howary Radiology Centre, Benghazi in the period between the 1st of April 2018 and the 31st of March 2019. Participants in the sample were purposively selected. Data was then collected and transferred to SPSS Software Version 23 and the analysis was completed. An independent sample t-test was used to examine the differences between two independent groups and the relationships between two independent categorical variables was examined through chi-square analysis. ANOVA was used to compare more than two means. The morphology of the Sella Turcica appeared to be normal in shape in 36.3% of males and 31.3% of females. The oblique anterior wall was noted in 36.3% of males and 15% of females, the Sella Turcica bridge was recorded in 6.1% of males and 12% of females, the notching posterior wall of Sella was present in 1.2% of males and 31.3% of females and the pyramidal shape of dorsum Sella was recorded in 6.1% in males and 10.4% of females. There was no difference in the linear dimensions of Sella Turcica when the various age groups were compared, however, there was a difference in depth between age groups which was statistically significant (P= 0.001). The anatomy of the Sella Turcica and its surroundings is significant for neurologists and neurosurgeons with regard to their clinical assessments. The Sella shapes and dimensions reported in the current study can be used as reference standards for further investigations involving the Sella Turcica in Libyan subjects.